MODEL KEPEMIMPINAN MAJELIS ULAMA INDONESIA (MUI): SEBUAH TAWARAN UNTUK MASA DEPAN KEPEMIMPINAN TRANFORMATIF DI INDONESIA - Surahman Amin (Pascasarjana IAIN Sorong, 2020)
One of the important elements in community development is the ulama. The Ulama are duty bearers of the Prophets who rely on the implementation of their self-serving duties to Allah SWT. and the implementation of the duties of the Caliphate on earth in accordance with the will and guidance of Allah SWT. which was sent down to the Prophets and Apostles. The prophets and messengers were sent in turn to guide people to find their identity as religious creatures, which ended with the sending of the last Prophet and Rasul, Muhammad. After our Master Muhammad (s). passed away to Rahmatullah, then the apostolic mission that he carries until the end of time and for all mankind, is the responsibility of the scholars as heirs of the Prophets to continue this heavy but noble task until the end of time.